A hermenêutica jurídica (crítica) da tecnologia pós-moderna como resposta para o problema da compreensão, interpretação e aplicação do direito - Mozetic, Vinícius Almada (Universidade do Vale do Rio dos Sinos, 2016)
This research investigates the contribution of philosophy in the field of Law. Authors such as Heidegger and Gadamer question the fundamentals of support of a culture of time or a technical world. Perhaps this is the most interesting point in Heidegger and Gadamer's practice, even as this technical and scientific progress is not metaphysical, but finished, is the ultimate destination of modern philosophy, which regards the world as the object of a relentless will to power and domination. Why decide to do the analysis of the technique and its influence in legal science, deepens the thought in Heidegger, in the first chapter, because he is largely responsible for that one could think of new fundamentals to justify a Legal Hermeneutics (critical) of technology. But it was necessary to go through the study of so-called fundamental ontology, which actually does not provide a new fundamental, but also arises from the fundamental of the fundamentals. So, all this questioning that is perceived in Heidegger - who already think in Being and Time, as the place where they discover several ways to interpret Being itself (not only ones) is going to grade a relationship between philosophy, technology and right; between hermeneutics, philosophy, technology and law. In the second chapter, it deals with the main impact of technology in Law. This will happen so that you can understand the philosophy of technology within Law, the perspective of philosophical hermeneutics, ie, it happens legal hermeneutics of technology as a result of this complexity. Therefore, it should be clear that the difference between traditional legal hermeneutics and legal hermeneutics of technology, object of this research [U1], should also be understood from the point of view of existential hermeneutics, that is through a interpretation process of what is influenced by technology, not only and directly in the texts, even virtualized, but the technological cases based on historical context variables under the false idea of efficiency which takes Brazilian court account; a path that is not covered only by a legal relativism, even for pre-interpretations of these virtual texts continue providing a new interpretation and application of a law, which are always conditioned to arbitrariness [U2], even though by tradition. This is what Gadamer calls "fusion" of horizons. For these reasons, understanding and reinterpretation of this phenomenology is of paramount importance, since it creates the possibility of a new phenomenological philosophy of technology in Law, a new e-language that goes beyond the classic diagnosis of alienation and that resides in Brazilian judiciary. Now, in the third chapter, the philosophy of technology of/in Law will be explored with emphasis, based on what is defended as a resurgence - a phoenix Hermeneutics - which will necessarily be more legal and more critical this dangerous crossing in the technical era. The approach method is inductive, being based on the study of theories and laws, verifying, through the methodological procedure of literature, doctrines, scientific articles and legislation, the possibility of using new technologies in law.
Keywords: Hermenêutica jurídica; Novas tecnologias; Pós-modernidade; Legal hermeneutics; New technologies; Postmodernity; ACCNPQ::Ciências Sociais Aplicadas::Direito